Madeira sobre mar - Adinolfi, Maurício Pinto [UNESP] (2015)
The work described in this dissertation refers to a characteristic of shared projects developed in areas where issues between nature and civilization are in constant conict. These interventions, that have paintings as a foundation, have been conducted with several partnerships, such as labor unions, government agencies and work cooperative groups. The main objectives of this work: a description of the action process, discussion about the location, the relationships built in the process, the various strategies used, as well the poetic influences. An Art Exhibition at the Art Institute of Unesp complete this work